A current focus on fibrotomy as a therapy to prevent recurrence in orthodontic treatments. A review - Anaya Espinoza, Sven Mario (2019)
This research is based on the review of a coadjuvant treatment to fixed or removable contention after orthodontic treatment to reduce recurrence. Post-orthodontic treatment recurrence is a common problem, especially in patients who had very rotated or tilted teeth, even in patients with fixed or removable retaining appliances. Currently, transseptal fibers are considered to be the cause of recurrences, especially oxythalanic ones, due to the position they adopt from the cementum-adamantine junction of a tooth to the same junction of the adjoining tooth, passing over the alveolar crest and due to their elastic characteristics. Supracrestal circumferential fiberotomy (SCS) emerges as an adjuvant therapy to reduce recurrence rates after orthodontic treatment. The objective of this literature review is to describe the current approach to fiberotomy as an efficient and stable long-term therapy to prevent recurrence in orthodontic treatments. The surgical technique has not changed, but there have been authors who seek to perform FCS with different instruments, such as electrosurgery and low-intensity diode laser. In the long term, there are no significant differences between the different instruments used for the FCS compared to the conventional one, but there are significant differences between performing the FCS and not performing it. FCS is an efficient and stable therapy regardless of the instrument used.